2014
DOI: 10.4103/0377-4929.130900
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant NDM-1 metallo-beta-lactamase producing Klebsiella pneumoniae sepsis outbreak in a neonatal intensive care unit in a tertiary care center at central India

Abstract: Co-production of NDM-1 with CTX-M-15 in K. pneumoniae isolates was detected for the first time in our NICU. Transmission of plasmid carrying these resistant genes to other members of Enterobacteriaceae will increase the incidence of multidrug resistance. Early detection of these genes will help in prevention and adequate infection control by limiting the spread of these organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
2
9
1
Order By: Relevance
“…These results concur with another genotyping study of carbapenem-resistant K. pneumoniae, which used pulsed field electrophoresis and found clone dissemination in 2009 and 2013 in the ICU of the same hospital (37). Other researchers worldwide have also reported the spread of a clone of NDM-1-producing K. pneumoniae in ICUs (25), confirming that hospitalization in the ICU is a determining risk factor for the acquisition and dissemination of these pathogens.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results concur with another genotyping study of carbapenem-resistant K. pneumoniae, which used pulsed field electrophoresis and found clone dissemination in 2009 and 2013 in the ICU of the same hospital (37). Other researchers worldwide have also reported the spread of a clone of NDM-1-producing K. pneumoniae in ICUs (25), confirming that hospitalization in the ICU is a determining risk factor for the acquisition and dissemination of these pathogens.…”
Section: Discussionsupporting
confidence: 88%
“…Although advanced age is considered a risk factor for acquiring carbapenem-resistant enterobacteria (23), in the present study none of the patients were elderly. NDM + KPC K. pneumoniae have been found to cause infections regardless of patient age in other studies (25). However, two patients had underlying diseases (systemic lupus erythematosus and diabetes mellitus) that compromise immunity and favor the establishment/development of infections and death by these multidrug resistant bacteria (26).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It was reported that the bla NMD‐1 gene was in the coding sequence of plasmid. There were often some other resistance genes inserted around the coding sequence . Thus, it was a complex resistant phenotype to bla NDM‐1 ‐positive isolates.…”
Section: Discussionmentioning
confidence: 99%
“…7 South Asia is one potential reservoir for these genes, with an NDM carriage prevalence of 14% in outpatients and 27% in hospitalized patients reported in Pakistan 8 and NDM-1 genes detected in 4% of drinking water and 30% of waste seepage samples from New Delhi, India. 9 Most published descriptions of clinical outbreaks have been associated with NDM-positive K. pneumoniae or Escherichia coli 10,11 and, again, large outbreaks are typically thought to be clonal using a variety of typing methodologies, including repetitive-PCR or high-resolution typing with whole-genome sequencing (WGS). 12 …”
Section: Introductionmentioning
confidence: 99%